Bombardier beetles of the genus Pheropsophus Solier 1833 (Carabidae: Brachininae: Brachinini) from Indian subcontinent - Venugopal, Akhil S.; Thomas, Sabu K. (Zootaxa, 2019)
Key to the 22 species of genus Pheropsophus Solier 1833 of Indian subcontinent with diagnostic characters, notes, new synonyms, distribution patterns and record of two new species—Pheropsophus devagiriensis sp. nov. and P. indicus sp. nov.—from south west India are provided. Synonymisation of Pheropsophus discicollis (Dejean 1826) with Pheropsophus hilaris (Fabricius 1798) syn. nov., clearing the complications regarding the taxonomy of P. hilaris and P. sobrinus by tracking down the type series of P. hilaris, and reinstating the species status of Pheropsophus sobrinus (Dejean 1826) are the other outcomes of the present study.                Out of the 22 species recorded in India, 14 species are confined to Oriental realm and rest of the eight species penetrates into the Palearctics also; 10 (of the 22) are endemic to Indian subcontinent with P. indicus sp. nov. endemic to south western India; P. devagiriensis sp. nov. endemic to the Western Ghats; P. andrewesi, P. krichna and P. prophylax are endemic to the Indo-Burma; and P. nanodes and P. scythropus are endemic to the Eastern Himalayas.